Utilization of Natural Polyelectrolytes in the Preparation of Naproxen as Sustained Release Matrix Tablet - Zahraa Oleiwi Hamzah; Wedad k. Ali (College of Pharmacy / Mustansiriyah University, 2019)
Our study demonstrates the preparation of naproxen as a sustained release matrix tablet using polyelectrolyte complexes PECs.The cationic polymer used in this study is chitosan CS while the anionic polymer includes sodium alginate SA, xanthan gum XG or carrageenan CG as anionic polymers. FT-IR spectra of these   complexes were studied to indicate the interactions between polyions. Precompression and compresion parameters were studied including the flowability, tablet hardness, thickness, friability, weight variation, drug content and in vitro release study. The results showed that the release rate of naproxen was decreased in the formulas that contains the physical mixtures comparing to the formulas with single polymer and the formula containing high molecular weight chitosan: xanthan gum CSh: XG physical mixture in 3:1 ratio formed the strongest PEC in which the release rate extended up to 20 hr. In conclusion, this work succeeded in preparation of naproxen as oral sustained release matrix tablet, using a physical mixture of cationic and anionic polymers to form PECs resulting in less frequent dosing and a reduction in gastric irritation.